Fake-love: brand love for counterfeits. Issue 6 (8th June 2018) - Khandeparkar, Kapil; Motiani, Manoj
Abstract : Purpose: Recent studies have indicated that consumers who knowingly purchase counterfeits could be in love with the brands whose counterfeits they own. Arguably, this love may not be the same as the love felt by individuals who purchase the original brand. Research in this field has not studied how these two love types differ in its genesis and consequences. Therefore, the paper aims to discuss this issue and intends to fill this gap. Design/methodology/approach: This study performed a multi-group analysis using (PLS-SEM) between two groups of customers (real-buyers and fake-buyers) to elucidate the factors that separate fake-love from real-love. This study adopted a combination of convenience sampling and field visits to identify 500 individuals who were classified as either real-buyers or fake-buyers. Findings: The relationship between social-self and brand love is significantly stronger for fake-buyers as compared to real-buyers. However, the relationship between inner-self and brand love is significantly stronger in the case of real-buyers as compared to fake-buyers. Real-buyers tend to be more brand resilient than fake-buyers as their love emanates primarily from the inner-self. Additionally, fake-buyers indulge in +WOM more than real-buyers as their brand love emanates from the social-self. Originality/value: This is the first study to explore the concept of brand love among consumers who purchase counterfeits in spite of being able to afford the original brands. This is also the first study that is focused on identifying the antecedents and outcomes that separate real-love from fake-love.